Fusões e aquisições de companhias brasileiras em anos recentes: um estudo dos fatores determinantes sob a ótica da empresa adquirente - Natália Garcia de Oliveira (2016)
Mergers and acquisitions - M&As are carried out with different objectives, normally these operations comprise the corporate strategy with the purpose of obtaining financial, operational, strategic and technological gains. Considering the fact that the organizational environment is characterized by a great dynamism, companies need to remain competitive, guaranteeing the generation of value for shareholders and products and services for society. On the other hand, it is clear that the results and reasons that permeate such strategies are still gaps to be filled in the academic world. Therefore, this work was elaborated with the objective of identifying the determining factors for mergers and acquisitions involving Brazilian acquiring companies, listed on BM&FBOVESPA between 2010 and 2015. For this, economic, financial and market data were analyzed in 130 M&As processes, for a sample of 75 companies, divided into two groups: Group A: 50 companies that made M&As between 2010 and 2015 and Group B: 25 companies that do not Held M &As between 2008 and 2015.Twelve variables were used as proxies: i) of value creation: ii) the obtaining of synergies; iii) of the tax benefits; iv) business leverage; v) of the alternative to dividends and repurchase of shares; vi) anticompetitive effects and monopoly power; vii) excessive management pride; viii) cost of replacement and market value; ix) company size; x) of the family control; xi) joint capital control; xii) of the industry segment. In methodological terms, initially, a descriptive analysis was carried out to evaluate the behavior of explanatory variables over time. For this purpose, dispersion diagrams were plotted with non-parametric regression adjustment using the Locally Weighted Scatterplot Smoothing method - LOWESS. In parallel, for the identification of the factors that determined the M&As realization, we opted for the use of the Logit Model of Grouped Effects (GEE), in which the dependent variable is binary. In the end, 10 hypotheses were tested, the conclusions indicate that, the determining factors for F & As were: i) Shareholder Value Creation: companies with greater potential for value creation are more prone to M&As; ii) Dividend Distribution and / or Share Repurchase Policy: companies with a high Payout ratio are more likely to perform M&As (a sign that is contrary to expectations); iii) Cost of Replacement and Market Value: companies with high Q of Tobin, (greater than 1), are more likely to carry out M&As; iv) Size of the Company: larger companies are more likely to carry out M&As. Additionally, it has been verified that time is a factor to be observed when M&As operations occur. The contribution of this research consisted in identifying the determinants for the realization of F & As, from a theoretical model, and not only, to verify the results obtained after the accomplishment of such operations.